IMPROVING STUDENT"™S SPEAKING ABILITY THROUGH ROLE PLAY MODEL FOR ESP STUDENTS - Ukhrowi, Wim Banu (Jurnal Kajian Pembelajaran dan Keilmuan, 2022)
This research is designed as research on improving students' speaking ability for students of the undergraduate nursing program. This research used Role-play as a technique in teaching speaking in English course. The method of this research is called"   A   Classroom   Action   Research".   The subject of this research was the undergraduate nursing program in the academic year   2021-2022   semester 5 consisting of   24   students.   The data of this research were collected by using a measurement technique that was a performance test to measure students' achievements. The findings of this classroom action research showed that speaking ability in class increases by using the Roleplay technique. Based on data analysis, the mean score of the students on the first cycle is 6.770, which qualified poor to average, and the mean score of the students on the second cycle is   7.406, which is qualified average to good. It means that the action hypothesis of the using Role play technique to improve students' speaking ability in class is proven.